The Suburban Squeeze: Land Conversion and Regulation in the San Francisco Bay Area - Dowall, David E (California Series in Urban Development, 2023)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1984.